INNV-48. TUMOR TREATING FIELDS UTILIZATION IN A GLIOBLASTOMA PATIENT WITH A PREEXISTING CARDIAC PACEMAKER: THE FIRST REPORTED CASE. (5th November 2018) - McClelland, Shearwood; Henrikson, Charles; Ciporen, Jeremy; Jaboin, Jerry; Mitin, Timur
Abstract: INTRODUCTION: Tumor treating fields (TTF) have become an important, evidence-based modality in the treatment of glioblastoma (GBM). In patients requiring cardiac pacemakers, TTF therapy is complicated by theoretical concerns regarding a possible electrical interaction between the devices. The authors report a GBM patient with an indwelling cardiac pacemaker who underwent successful TTF application. METHODS: A 57-year-old man with past medical history of sick sinus syndrome requiring cardiac pacemaker implantation suffered an acute neurologic change and was found on imaging to have a left parieto-occipital lesion, which following his second surgery was found to be GBM. After completion of guideline-concordant chemoradiation, he chose to undergo TTF therapy. Because of the absence of cardiac symptoms and the theoretical risk of far-field sensing by the pacemaker of the TTF device, potentially resulting in pacemaker inhibition, the pacemaker was turned off prior to receiving TTF. RESULTS: Following TTF implementation, the patient responded well; he remains alive more than 25 months following his GBM diagnosis, exceeding the median 20.9 month survival of the recently completed phase III TTF randomized clinical trial for newly diagnosed GBM. Furthermore, he has exhibited neither cardiac morbidity nor adverse scalp reactions to TTF therapy. CONCLUSIONS: The first reported case of successful TTF administration in a GBM patient with a previously implanted cardiac pacemaker may allay the concerns of neuro-oncologists, cardiologists, radiation oncologists, and all certified TTF prescribers regarding the applicability of TTF in suitable candidates with preexisting cardiac pacemakers. This case indicates that TTF therapy is efficacious in patients with indwelling MRI-conditional cardiac pacemakers turned to the off position, and that physical removal of the pacemaker is not necessary prior to starting TTF.